THERAPY OF DIARRHEA AND DEHYDRATION IN CHILDREN - E.G. Tsymbalova; R.F. Tepaev (Union of pediatricians of Russia, 2011)
Dehydration is one of the leading causes of mortality in children. The most frequent cause of dehydration in children is diarrhea syndrome. Timely differential diagnostics of etiological causes, assessment of severity, dehydration type are critical conditions of successful therapy of diarrhea syndrome. The article provides modern recommendations on diagnostics and treatment of dehydration depending on the type and severity, on correction of electrolyte abnormalities. The authors also highlight etiological and symptomatic therapy for diarrhea syndrome in children.Key words: diarrhea, dehydration, causes, hyponatremia, hypernatremia, rehydration, children.